"A Heat Pump Needs a Bit of Care": On Maintainability and Repairing Gender–Technology Relations. (November 2021) - de Wilde, Mandy
As part of current energy transitions in the Global North, households have begun adopting renewable energy technologies, such as heat pumps and solar power systems, in significant numbers. These changes give rise to the following question: how are technology and gender configured when new technologies enter everyday life? Based upon ethnographic fieldwork on interactions between households, technologies, and technicians and interviews with sales technicians, installers, and service mechanics, I demonstrate how both stable and fragile variants of renewable energy technologies are enacted during prepurchase consultations and postpurchase installations, respectively. I employ science and technology studies scholarship, feminist ethics, and repair and maintenance studies—captured through the analytical lens of care—to analyze how technicians mobilize and tinker with gendered affection, knowledge, and action in households to effectuate adoption of renewable energy technologies. I clarify how, in this process, openings are created to configure both hegemonic and heterogeneous gender–technology relations. Finally, I advance discussion beyond gender issues by arguing that acknowledging the role of maintainability and the repair of user–technology relations in current energy transitions opens pathways not only for exploring gender in new and exciting ways in relation to technology but technician–user relationships as well.